SANKSI PIDANA MATI BAGI TINDAK PIDANA KORUPSI: RESPONSI DAN IJTIHAD HUKUM ISLAM - Zainuddin, Muhadi (Al-Mawarid Jurnal Hukum Islam, 2012)
The results ofresearch conductedby variousinstitutions, one of the is Political and Economic Risk Consultancy (PERC),showedthat the levelof corruptioninIndonesia,with itsmuslim majority,is the highestin the world.Corruptionnotonlyhas hurtstate finances, weakenthe countryâs economyandhampernationaldevelopmentbut alsohas damagedthe nationmentality. The Impact of this crime runs in many aspect of life, such as political aspects, law aspects, cultural aspectandeducational aspect. To avoiding this crime, we need big punishment for corruption criminal. Corruptionisakhiyanahcrimebecauseits characterthat is distorting the trust from the other (state).InIslamiccriminal law, khiyanahcrimesfall into the categoryof non-definitivecrime (jarimah ghair mahdudah) whichits criminalsanctionshanded tothe judgeâsijtihadbasedon the justness anddeterrenteffect. Keywords: corruption, khiyanah, non definitive crime (jarimah ghair mahdudah), taâzÃ®r.